Faith in law, law in faith: reflecting and building on the work of John Witte, Jr - Witte, John (Brill | Nijhoff, 2024)
"Across four decades, John Witte, Jr. has advanced the study of law and religion by retrieving religious sources of law, renewing timeless teachings of religion for today, and reengaging with the difficult issues confronting society. Interdisciplinary, international, and interfaith in scope, Witte's work has generated an enormous body of scholarship. This collection of essays by leading scholars examines his impact and maps new directions for future exploration"--